The Influences of Sports Viewing Conditions on Enjoyment from Watching Televised Sports: An Analysis of the FIFA World Cup Audiences in Theater vs. Home. Issue 3 (2nd July 2016) - Kim, Kihan; Cheong, Yunjae; Kim, Hyuksoo
Abstract : This study investigates how experiences of viewing sports content in a movie theater differ from typical television viewing conditions in a home. The results of analyses showed that the viewing condition (theater vs. home) influenced audiences' sense of presence when watching mediated sports, which, combined with the attractiveness of the game, would determine the suspenseful nature of the media experience, as well as the subsequent enjoyment.